1990
DOI: 10.1002/pssb.2221600118
|View full text |Cite
|
Sign up to set email alerts
|

Positron Distribution in Semiconductors

Abstract: The positron distribution of charge along the (1 11) direction is calculated for elemental and compound semiconductors. The results show that the positron has a strong affinity for one sort of atom in binary semiconductors. This relative positron affinity may lead to the positron preferentially annihilating with the electrons of that sort of atom in compound semiconductors. The trends in going from Ge to CdTe through GaAs show an increase in positron affinity for the anion over the cation.La densite de charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The coefficients Cnk(C) are obtained by solving the Schrodinger equation. Similarly the positron wave function, is obtained in the same way as given by Aourag et al [7]. In terms of the electron and positron wave functions one can write e2'(p) as where…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…The coefficients Cnk(C) are obtained by solving the Schrodinger equation. Similarly the positron wave function, is obtained in the same way as given by Aourag et al [7]. In terms of the electron and positron wave functions one can write e2'(p) as where…”
Section: Theorymentioning
confidence: 98%
“…The positron-electron correlation potential was not taken in our calculation of the positron wave function. In the recent calculation of positron densities in compound semiconductors [7] it was found that the positron density is nearer to the anion site. In the case of ionic solids it was also found [8] that the positrons annihilate mostly near the anion.…”
Section: Introductionmentioning
confidence: 97%
“…The positron wave function was determined through the ionic potential using the point-core approximation [40,52]. With the potential diverging at the ion core region the wave function is expected to converge with a high number of plane waves.…”
Section: Calculationsmentioning
confidence: 99%
“…Si and Ge by different groups [33 to 39]. Since compound semiconductors are covalent materials with a degree of ionicity, they are expected to show different behavior compared to group-IV semiconductors, since the probability of the positron annihilating with the negative ion is greater than that with the positive ion [40]. In the case of ionic solids it was also found [41] that the positrons annihilate mostly near the anion.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear charge can be expressed as a d-function at the origin of each cell. We shall adopt the point core approximation [11].…”
Section: Formalismmentioning
confidence: 99%